Strategy for Implementing New Technology to Improve Supply Chain Management Efficiency: A Systematic Literature Review - Dewa Ayu Sri Arimas Dewi (The Journal of Management, Digital Business, and Entrepreneurship, 2026)
The use of information technology in supply chains is becoming increasingly important due to several factors, such as the growing complexity of supply chains. Supply chains have become complex due to factors like globalization and market volatility, which necessitate the implementation of digitalization to enhance visibility and agility across the entire supply chain network. This research aims to explore strategies for implementing new technology to improve supply chain management efficiency through a Systematic Literature Review (SLR) approach. The transformation driven by Industry 4.0 technologies—such as artificial intelligence (AI), the Internet of Things (IoT), and blockchain—has presented significant challenges and opportunities. This study highlights the importance of sustainability in automation implementation by balancing economic efficiency, environmental sustainability, and social welfare. By synthesizing findings from various studies, this research offers policy recommendations that support sustainability and social inclusiveness, as well as strategic guidance for the industry on adopting supply chain automation in a sustainable manner.